Potential of locally available products for use as binders in producing fecal compost pellets in Ghana - Nikiema, Josiane; Cofie, Olufunke O.; Asante-Bekoe, Barbara; Otoo, Miriam; Adamtey, Noah (Wiley, 2014)
Market studies in Ghana have revealed a potential for composted or cocomposted fecal matter as nutrient source inputs for agricultural production. To increase the marketability of such products, high nutrient value and easier handling/transporting options are among the significant factors which drive demand. Pelletization is seen as a potentially interesting option to address these challenges. To preserve form stability of the pellet products, the addition of a binding material during the pelletization process is crucial. In Ghana, water, beeswax, clay, and cassava starch have been identified as locally available binding materials. A comparative assessment of these materials as a premier binder suitable for pelletization was performed based on predefined criteria. Quantitative criteria considered included the total amounts available, the seasonal variation during the year and cost. Qualitative criteria such as handling and storage conditions, ease of use during pelletization, and the binding ability were also evaluated. Based on this assessment, clay and cassava-based starch were selected as the most promising binding agents. Currently, clay is abundant in Ghana and this may suggest a guarantee for consistent and stable supply over coming years. However, from the perspective of cassava-based starch, this situation depicts limited production of starch and competition on the local markets.